Relativism in Feyerabend's later writings. (June 2016) - Kusch, Martin
Abstract: This paper reconstructs, and distinguishes between, Feyerabend's different forms of relativism in his later writings. Science in a Free Society remains close to familiar forms of relativism, while, at the same time, developing an original but under-argued form of political relativism, and rejecting "conversion" models of cultural exchange. Farewell to Reason moves away from common renderings of relativism, and develops a range of different new forms. Central here are links between relativism, skepticism and infallibilism. In the last six years of his life, Feyerabend often criticizes a peculiar radical form of relativism that arguably no-one has ever proposed or defended. In the same context, Feyerabend sketches an "ontological" form of relativism. It combines "Kantian humility", metaphysical pluralism and constructivism. Highlights: This paper reconstructs Feyerabend's different 'relativisms' in his later writings. Science in a Free Society remains close to familiar forms of relativism. Farewell to Reason moves away from common renderings of relativism, and develops a range of different new forms.